1996
DOI: 10.1161/01.cir.94.5.1018
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Defined Therapy of Inherited Long-QT Syndrome

Abstract: An increase in serum potassium corrects abnormalities of repolarization duration, T-wave morphology, QT/ RR slope, and QT dispersion in patients with chromosome 7-linked LQT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(43 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…25,26 In oocytes bathed by Kϩ concentrations ranging from 0.5 to 20 mmol/L, HERG current amplitude varied as a linear function of [Kϩ]e. 27 Unlike most other Kϩ currents, the magnitude of outward HERG current is paradoxically reduced on removal of extracellular Kϩ, thus explaining the increased action potential and prolonged ventricular repolarization in hypokalemic patients. In addition, an increase in serum potassium corrects or reduces part of the abnormalities of repolarization in patients with chromosome 7-linked LQT, 28 which was the case in our patients. Yang et al showed that the IKr blocking effects of quinidine and dofetilide, 2 antiarrhythmic agents, are increased by low extracellular potassium concentration.…”
Section: Discussionsupporting
confidence: 71%
“…25,26 In oocytes bathed by Kϩ concentrations ranging from 0.5 to 20 mmol/L, HERG current amplitude varied as a linear function of [Kϩ]e. 27 Unlike most other Kϩ currents, the magnitude of outward HERG current is paradoxically reduced on removal of extracellular Kϩ, thus explaining the increased action potential and prolonged ventricular repolarization in hypokalemic patients. In addition, an increase in serum potassium corrects or reduces part of the abnormalities of repolarization in patients with chromosome 7-linked LQT, 28 which was the case in our patients. Yang et al showed that the IKr blocking effects of quinidine and dofetilide, 2 antiarrhythmic agents, are increased by low extracellular potassium concentration.…”
Section: Discussionsupporting
confidence: 71%
“…These findings correlate with earlier studies that focused on HERG current density, showing that I Kr current paradoxically increased when extracellular K + concentration was increased (Sanguinetti & Jurkiewicz, 1992). One group administered spironolactone to eight LQT2 patients for four weeks, and observed a decrease in QT interval, (Etheridge et al, 2003) while another treated seven subjects with potassium supplementation and had similar findings (Compton et al, 1996). Such approaches may be considered in LQT2 patients.…”
Section: Therapeutic Approachessupporting
confidence: 86%
“…Potassium channel activators, such as nicorandil or pinacidil, have been shown to reverse epinephrine-induced QT prolongation and suppress ventricular arrhythmias (36,37). In LQT2, shortterm, exogenously administered potassium was reported to correct QT abnormalities in affected patients (38), presumably by enhancing IKr in the outward direction across the cell membrane. Recently, long-term oral potassium administration was shown to improve repolarization abnormalities in LQT2 patients (39).…”
Section: Therapeutic Considerationsmentioning
confidence: 99%